Implementation of Value Engineering in Bandung Islamic University Hospital Building Construction - Salman Faruq, Reza; Sri Handayani, Fajar; Setiono, Setiono (Sustainable Civil Building Management and Engineering Journal, 2024)
Infrastructure development in Indonesia has increased sharply every year. Construction projects are starting to appear at a fairly high frequency in each region. However, in the process of project development, the quality, time, and cost aspects are not always optimal. Therefore, Value Engineering analysis is needed to get optimal results. This Value Engineering analysis is able to identify components that can be saved and determine alternatives to replace these components without reducing the quality or quality of work. The case study in this research is the Bandung Islamic University Hospital Construction Project. The Value Engineering analysis carried out on this project is a change in the work of the upper structure, such as slab, column and beam from conventional to precast concrete. In addition to Value Engineering analysis, this research also analyzed greenhouse gas emissions using Life Cycle Assessment analysis. The results showed savings of Rp 3,180,685,659.81 or 8.19% of the initial project cost. Meanwhile, the existing greenhouse gas emissions amounted to 9556.01 kgCO2e and for alternative work amounted to 72896.49 kgCO2e.